2015
DOI: 10.3892/or.2015.4450
|View full text |Cite
|
Sign up to set email alerts
|

miR-331-3p inhibits proliferation and promotes apoptosis by targeting HER2 through the PI3K/Akt and ERK1/2 pathways in colorectal cancer

Abstract: MicroRNAs (miRNAs) regulate cell proliferation, apoptosis and carcinogenesis by targeting related mRNAs in different types of cancer. miR-331-3p has been found to regulate the development and progression of various types of cancer cells. However, little research has been conducted on the role of miR-331-3p in colorectal cancer (CRC). The present study aimed to explore the function of miR-331-3p in CRC. We found that miR-331-3p was significantly downregulated in CRC tissues and cells compared to the level in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 42 publications
1
65
0
2
Order By: Relevance
“…In addition to siRNA, miRNAs are also potential vectors for HER2 silencing. For example, miR-331-3p has recently been shown to reduce proliferation and increase apoptosis in colorectal cancer cells via HER2 silencing 36 . Small RNA loading into EVs via sonication enables increased options for delivery of both siRNA and miRNA against HER2 and other oncogenes, and thus may be useful in a variety of cancer therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to siRNA, miRNAs are also potential vectors for HER2 silencing. For example, miR-331-3p has recently been shown to reduce proliferation and increase apoptosis in colorectal cancer cells via HER2 silencing 36 . Small RNA loading into EVs via sonication enables increased options for delivery of both siRNA and miRNA against HER2 and other oncogenes, and thus may be useful in a variety of cancer therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 is a known pro-inflammatory lipid mediator and promotes tumor progression via several mechanisms such as regulation of cell proliferation, induction of tumor cells to secrete growth factors, and immunomodulation for the escape of tumor cells from effective immunosurveillance [165]. Zhao et al [166] examined different human colon cancer cell-lines, e.g. HCT116, LoVo, HT-29, SW480, DLD-1 and Caco-2; and found that HER2 was overexpressed in these cells.…”
Section: Tumors Of Other Organs and Her2 Expression Malignant Diseasementioning
confidence: 99%
“…1 MiRNAs not only can act as oncogenes and tumor suppressors directly 4,5 but also play a role in COAD by regulating the expression of their targeting genes. 6,7 Hence, identifying the key miRNAs in early-stage COAD is also crucial. With advanced high-throughput technology, both RNA-sequencing and microarray analysis can be used to identify differentially expressed genes (DEGs) and miRNAs (DEmiRNAs).…”
Section: Introductionmentioning
confidence: 99%